Training guide. Gender and Climate Change Research in Agriculture and Food Security for Rural Development - Nelson, S.; Chaudhury M; Tranberg H; Lambrou Y; Tapio-Bistrom, M.L.; Kristjanson, Patricia M. (CGIAR Research program on Climate Change, Agriculture and Food Security (CCAFS). Food and Agriculture Organization of the United Nations (FAO)., 2011)
The purpose of this guide is to promote gender-responsive and socially-sensitive climate change research and development in the agriculture and food security sectors through participatory approaches. The guide focuses on the household and community level. It provides users with resources and tools for collecting, analysing and sharing gender-sensitive information about agricultural communities, households and individual household members who are facing climatic changes.